Development of a core measurement set for research in degenerative cervical myelopathy: a study protocol (AO Spine RECODE-DCM CMS). Issue 6 (9th June 2022) - Davies, Benjamin M; Yanez Touzet, Alvaro; Mowforth, Oliver D; Lee, Keng Siang; Khan, Danyal; Furlan, Julio C; Fehlings, Michael G; Harrop, James S; Zipser, Carl Moritz; Rodrigues-Pinto, Ricardo; Milligan, James; Sarewitz, Ellen; et al.
Abstract : Introduction: Progress in degenerative cervical myelopathy (DCM) is hindered by inconsistent measurement and reporting. This impedes data aggregation and outcome comparison across studies. This limitation can be reversed by developing a core measurement set (CMS) for DCM research. Previously, the AO Spine Research Objectives and Common Data Elements for DCM (AO Spine RECODE-DCM) defined 'what' should be measured in DCM: the next step of this initiative is to determine 'how' to measure these features. This protocol outlines the steps necessary for the development of a CMS for DCM research and audit. Methods and analysis: The CMS will be developed in accordance with the guidance developed by the Core Outcome Measures in Effectiveness Trials and the Consensus-based Standards for the selection of health Measurement Instruments. The process involves five phases. In phase 1, the steering committee agreed on the constructs to be measured by sourcing consensus definitions from patients, professionals and the literature. In phases 2 and 3, systematic reviews were conducted to identify tools for each construct and aggregate their evidence. Constructs with and without tools were identified, and scoping reviews were conducted for constructs without tools. Evidence on measurement properties, as well as on timing of assessments, are currently being aggregated. These will be presented in phase 4: a consensus meeting where a multi-disciplinary panel of experts will select the instruments that will form the CMS. Following selection, guidance on the implementation of the CMS will be developed and disseminated (phase 5). A preliminary CMS review scheduled at 4 years from release. Ethics and dissemination: Ethical approval was obtained from the University of Cambridge (HBREC2019.14). Dissemination strategies will include peer-reviewed scientific publications; conference presentations; podcasts; the identification of AO Spine RECODE-DCM ambassadors; and engagement with relevant journals, funders and the DCM community.